Techno-economic analysis of biodiesel production from palm, Jatropha curcas and Calophyllum inophyllum for road transport in Malaysia / Ong Hwai Chyuan - Ong, Hwai Chyuan (2012)
Transportation sector has a dominant role in global fuel consumption and greenhouse gas emissions. Due to the dramatic increase in greenhouse gas emission, sustainable development of this sector has raised the concern in many countries including Malaysia. Biodiesel is a renewable energy that has great potential to serve as an alternative fuel to fossil diesel in the compression ignition (CI) engine. Although Malaysia is one of the biggest biodiesel fuel producers, the commercialization of biodiesel has not been fully undertaken in a large scale. Besides the technical barriers, there are several nontechnical limiting factors, which impede the development of biodiesel. A wide variety of biodiesel research on transesterification, performance and emission analysis is currently available worldwide. However, the study on techno-economic and feasibility of biodiesel fuel for Malaysian condition is limited. Therefore, this study is focused on biodiesel production and techno-economic comparison among palm, jatropha curcas and calophyllum inophyllum biodiesel as transportation fuel in Malaysia. Moreover, the present study attempts to find out the impact of biodiesel implementation towards the energy scenario, environmental and economy. The total CO2 equivalent emissions for road transport are 59,383 million kg. Therefore, alkaline catalyst transesterification process is used to produce palm, jatropha curcas and calophyllum inophyllum biodiesel as biofuel for road transport vehicles. It was found that the life cycle cost for 50 ktoe palm, jatropha curcas and calophyllum inophyllum biodiesel production plant with an operating period of 20 years is $764, $583 and $604 million respectively. The largest economic factor for biodiesel production is feedstock cost. Furthermore, replacing 5% of diesel with biodiesel in road transport vehicles can reduce the CO2 emission up to 1200 million kg in year 2031.